ANALISIS KESALAHAN BERBAHASA PADA BERITA DI MEDIA ONLINE “FACEBOOK DAN INSTAGRAM” - wa mirna; Syaidah Syaidah (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2022)
ABSTRACTThis study aims to describe (1) phonological, morphological, syntactic, and semantic errors found in the Indonesian discourse on the Humanitarian Crisis and the Death of the Democratic Space under President Joko Widodo's leadership which was published by the Papuan Student Alliance-AMP on March 14, 2022 through the media. Facebook online, (2) phonological, morphological, syntactic, and semantic errors contained in the discourse "Equity and structuring the Mardika market" published by Aldis Loilatu on June 3, 2021 through Facebook online media, (3) phonological, morphological, syntax, and semantics contained in the discourse "Makassar has the potential for PSBB to return, the decision will be determined in the next two days" which was published by Makassar Info on January 29, 2021 through the online media Instagram, and (4) provided corrections and follow-up to language errors from in terms of phonology, morphology, syntax, and semantics contained in the Facebook post ok and instagram. The results of the analysis of language errors on Facebook and Instagram online media can be concluded that there are types of language errors in the fields of phonology, morphology, syntax, and semantics. The results of this study are first, the types of phonological, morphological, syntactic, and semantic errors found in the Indonesian discourse on the Humanitarian Crisis and the Death of the Democratic Space under President Joko Widodo's leadership published by the Papuan Student Alliance-AMP on March 14, 2022. , (2) the types of phonological, morphological, syntactic, and semantic errors contained in the discourse of "even distribution and arrangement of the Mardika market" published by Aldis Loilatu on June 3, 2021, and (3) types of phonological, morphological errors , syntax, and semantics on the discourse "Makassar has the potential for PSBB to return, the decision will be determined in the next two days" published by Makassar Info on January 29, 2021.   Keywords: language errors, online media, facebook, instagram